Assessing quality of life in diabetes: II – Deconstructing measures into a simple framework. (April 2017) - Tang, Tricia S.; Yusuf, Fardowsa L.A.; Polonsky, William H.; Fisher, Lawrence
Highlights: An updated review of diabetes-specific HRQOL instruments between 2006–2016. A simple framework for evaluating researchers' need and instrument characteristics. Selection framework includes eight core characteristics. This framework aids in appropriate scale selection and utilization of instruments. Abstract: A growing number of instruments measuring diabetes-specific health-related quality of life (HRQOL) have been identified in previous systematic reviews, the most recent being published in 2008. The purpose of this paper is report on an updated systematic review of diabetes-specific HRQOL measures highlighting the time period 2006–2016; to deconstruct existing diabetes-specific HRQOL measures into a simple framework for evaluating the goodness-of-fit between specific research needs and instrument characteristics; and to present core characteristics of measures not yet reported in other reviews to further facilitate scale selection. Using the databases Medline, Pubmed, CINAHL, OVID Embase, and PsycINFO, we identified 20 diabetes-specific HRQOL measures that met our inclusion criteria. For each measure, we extracted eight core characteristics for our measurement selection framework. These characteristics include target population (type 1 vs. type 2), number and type of HRQOL dimensions measured and scored, type of score and calculation algorithm, sensitivity to change data reported in subsequent studies, number of survey items, approximate time length to complete, number of studies using the instrument in the past 10 years, and specific languages instruments is translated. This report provides a way to compare and contrast existing diabetes-specific HRQOL measures to aid in appropriate scale selection and utilization.